(untitled) (Antologia di Diritto Pubblico, 2024)
The paper dedicates some reflections to the well-known 1933 essay in which Gaspare Ambrosini on one hand outlines the creation of a new State model and on the other provides some useful methodological indications for the study of State forms. With regard to the first aspect, referring to the solutions offered by two European systems, the author proposes an intermediate model of State between the unitary and the federal State, setting out some firm points but at the same time leaving open several questions that still engage Italian politicians and scholars today. As to the second aspect, he urges scholars to always place the analysis of institutions in the space-time dimension in which they are inserted and, more generally, not to give up in the sometimes complex attempt to proceed with classifications. In both aspects mentioned above, Ambrosini’s words are characterized by their enduring relevance.